Rice genotypic variation in methane emission patterns under irrigated culture - Islam, M Rafiqul; Siddique, Imran Ahammad; Ali, Md Haidar; Islam, Md. Rafiqul; Mahmud, Abdullah Al (Fundamental and Applied Agriculture, 2018)
Anthropogenic emission of methane under anaerobic condition of irrigated rice field is a global concern contributing to global warming more than any other greenhouse gases. A field experiment was conducted with eight rice genotypes to identify the genotype(s) with low methane emission coupled with high yielding potential. Emissions of methane were measured from all treatments using manual operated closed chamber technique following standard guidelines and CH4 concentrations in the collected air samples were measured by gas chromatography. Methane emissions during different growth stages of rice ranged between 43.6 and 579.2 mg CH4 m−2 d−1 and showed a higher emission at maximum tillering to flowering stages, while peaks in CH4 fluxes were observed in 67 DAT for short duration and 84 DAT in long duration rice genotypes. Root biomass and growth duration showed significant positive correlation with methane emission (p<0.01), but above ground biomass had no significant effect on methane emission. The highest cumulative CH4 emission (257.6 kg CH4 ha−1) was noted in BRRI dhan29 having grain yield of 6.55 t ha−1, while the lowest (158.9 kg CH4 ha−1) was found in local variety, Kheyaliboro having grain yield of 3.04 t ha−1. Kheyaliboro showed lower methane emission but the lower grain yield contributed to the higher yield scaled methane emission. While quantifying yield scaled methane emission, considering the national food secu- rity, eight rice genotypes followed the order: Kheyaliboro>BR16>Binadhan- 6>BRRI dhan29>Binadhan-10>BRRI dhan28>BRRI dhan55>Binadhan-17. Yield scaled methane emission decreased by 14-45% in response to different rice genotypes. Employing yield scaled methane emission can address both climate change and national food demand.